Pola Warna Hasil Persilangan Kambing Boer dengan Kambing Jawarandu - G Husnu; I Panjaitan; T Rumiyani (Politeknik Negeri Lampung, 2023)
: This research aims to know the pattern of Boerja goat color which is the result of the crossbreeding of Boer goats with Jawarandu goats. This research was conducted at the Edrian Bulle Farm, Lampung. The object of this research used livestock material of 303 Boerja goats which consists of 217 F1, 56 F2, 19 F3, and 11 F4. The parameters include the color composition of the body part Boerja goat. The data that has been collected is processed and analyzed descriptively. The result of this research illustrates that the color that appears in Boerja goat are brown and white. The Boerja goat has a brown and white head and neck, while the Boerja goat has white fur on the surface of the body, legs, and tail. In general, the Boerja goat's color is a combination of Jawarandu goat color that spread following the pattern of Boer goat color.